Case report: Recurrent angioedema: Diagnosing the rare and the frequent - Buttgereit, Thomas; Fijen, Lauré M.; Vera, Carolina; Bergmann, Karl-Christian; Maurer, Marcus; Magerl, Markus (Frontiers in Medicine, 2022)
Hereditary angiodema with normal C1 inhibitor and unknown mutation (HAE-nC1INH-UNK), an exceedingly rare subtype of HAE, appears to be often diagnosed in patients who do not have this condition, but have mast cell-mediated angioedema. Here, we report two patients diagnosed with HAE-nC1INH-UNK by their physicians, who referred them to our center for treatment continuation with costly kallikrein-kinin-system targeted therapies. We describe how we established the correct diagnosis of recurrent mast cell- mediated angioedema after thorough investigation of both patients and initiated effective treatment with omalizumab. Also, we present and discuss the consensus criteria for diagnosing the very rare condition HAE-nC1INH in light of recent research and based on our own clinical experience. In conclusion, HAE-nC1INH-UNK should only be considered after more common differential diagnoses, i.e. mast cell-mediated angioedema, have thoroughly been investigated and ruled out. This approach reduces both the patients’ disease burden and healthcare costs and contributes to meaningful research.